Design of integrated energy market cloud service platform based on blockchain smart contract. (February 2022) - Wang, Lei; Ma, Yichao; Zhu, Liuzhu; Wang, Xuli; Cong, Hao; Shi, Tiancheng
Highlights: The transaction and dispatch of energy (carbon) is realized through cloud technology, which avoids the problems of distrust and high cost existing in traditional third-party institutions. The combination of blockchain technology and Internet of things technology provides a new way of energy trade and dispatch, and expands to carbon trading. Use Antchain technology to improve the deposit speed of cloud service platform blockchain and reduce running costs. Abstract: Traditional integrated energy market has problems such as single transaction type, opaque dispatch subsidies, and lack of institutions that can provide professional and fair services in the integrated energy market. Therefore, based on the smart contract of blockchain, this paper designs the cloud service platform for integrated energy market. The participants in the integrated energy market are divided into integrated energy suppliers and integrated energy users. The two can use the Digital Currency Electronic Payment (DCEP) to trade energy (carbon) in the blockchain smart contract provided by cloud service platform, as well as implement decentralized intelligent dispatch by using blockchain Internet of things technology. The smart contract designed by Antchain is used to simulate the energy trading and dispatch process of cloud service platform, and the verifiable simulation results are given. It is proved that the integrated energy market cloud service platform based on the blockchain smart contract designed in this paper can effectively realize not only the security and convenience of energy trading, but also the efficiency and intelligence of energy dispatch.